2017
DOI: 10.3390/membranes7020025
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Electrolyte Membranes for Water Photo-Electrolysis

Abstract: Water-fed photo-electrolysis cells equipped with perfluorosulfonic acid (Nafion® 115) and quaternary ammonium-based (Fumatech® FAA3) ion exchange membranes as separator for hydrogen and oxygen evolution reactions were investigated. Protonic or anionic ionomer dispersions were deposited on the electrodes to extend the interface with the electrolyte. The photo-anode consisted of a large band-gap Ti-oxide semiconductor. The effect of membrane characteristics on the photo-electrochemical conversion of solar energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…evolution reaction under alkaline conditions. The performance of the aforementioned co-catalysts was studied in a complete PEC cell in the presence of an ionomer dispersion and an anionic membrane [46,47] to evaluate their effect under practical conditions.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…evolution reaction under alkaline conditions. The performance of the aforementioned co-catalysts was studied in a complete PEC cell in the presence of an ionomer dispersion and an anionic membrane [46,47] to evaluate their effect under practical conditions.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…Its properties were compared to IrRuOx [43,44] and La 0.6 Sr 0.4 Fe 0.8 Co 0.2 (LSFCO) [45] as benchmark catalysts for the oxygen evolution reaction under alkaline conditions. The performance of the aforementioned co-catalysts was studied in a complete PEC cell in the presence of an ionomer dispersion and an anionic membrane [46,47] to evaluate their effect under practical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency and durability to produce pure H 2 by photo-electrolysis may be improved by employing a solid polymer-electrolyte between the electrodes as a gas separator. This separation for polymer-electrolyte membrane fuel cells (PEMFCs) and their subcategories [ 19 , 20 , 21 , 22 ] has been known for many years whereas the employment of a solid-membrane electrolyte has been less studied for PEC applications [ 23 , 24 ]. Its implementation in a cost-effective tandem PEC architecture, able to capture a significant portion of the solar irradiation, is structured as photoanode/membrane/photocathode and the working mechanism has been discussed in detail in some recent work [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…High water permeation to allow for proper water management between cathode and anode according to the main conduction mechanism. Pros and cons of using protonic or anionic membranes for separating the electrodes, as well as the issues related to their transparency to use them in a tandem photo-electrolysis cell, have been evaluated [24]. A significant increase either in photocurrent or spontaneous cell photovoltage for the anionic-membrane-based cell was observed and correlated with better reaction kinetics.…”
mentioning
confidence: 99%
“…(i) The membrane-electrode assemblies were completed by using two different types of polymeric membranes, with either protonic or hydroxide ion conductivity. In a recent publication, Arico et al [31]used model TiO2-based photoanodes supported on a coated glass and exposed them to deaerated water. They showed that the electrolyte environment can strongly influence the surface of photoanodes during water splitting.…”
Section: Introductionmentioning
confidence: 99%